Devonian Carbonate of Telen River, East Kalimantan - Fransiskus Sugiaman; Ludy Andria (Ikatan Ahli Geologi Indonesia, 1998)
BSc Thesis submitted to Bandung Institute of Technology, 1990In 1925, the Dutch Colonial Government sent a scientific expedition team to East Kalimantan, which was called